Selective etching of metastable phase induced an efficient CuIn0.7Ga0.3S2 nano-photocathode for solar water splitting1. Issue 15 (21st April 2015) - Guan, Zhongjie; Luo, Wenjun; Feng, Jianyong; Tao, Qiuchen; Xu, Yao; Wen, Xin; Fu, Gao; Zou, Zhigang
<x xml:space="preserve">Abstract</x> The photocurrent of a CuIn0.7Ga0.3S2 nano-photocathode increases about 2–3 times after selective etching of a metastable CuAu ordering phase.